2018
DOI: 10.1021/acscatal.8b01296
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Palladium-Catalyzed [3C + 2C] and [4C + 3C] Intramolecular Cycloadditions of Alkylidenecyclopropanes

Abstract: This article may be used for non-commercial purposes in accordance with American Chemical Society Terms and Conditions for self-archiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…56 The authors recently demonstrated the Pd-catalyzed formation of desirable 5,7-and 5-5-bicyclic systems 4.3b/4.3c from simple diene-tethered alkylidenecyclopropanes 4.3a in good yields and enantioselectivities using Feringa's phosphoramidite ligand (Scheme 4.3a). 56,57 Interestingly, the (S,R,R)-ligand gave better enantioselectivities and higher selectivity for the (4+3)-cycloadduct over the (3+2)-cycloadduct compared to when the (R,R,R)-ligand was used. The authors propose that the Pd-catalyst oxidatively adds into the cyclopropane ring at the distal bond to form a metallocyclobutane 4.3d (Scheme 4.3b).…”
Section: Palladium Platinummentioning
confidence: 99%
“…56 The authors recently demonstrated the Pd-catalyzed formation of desirable 5,7-and 5-5-bicyclic systems 4.3b/4.3c from simple diene-tethered alkylidenecyclopropanes 4.3a in good yields and enantioselectivities using Feringa's phosphoramidite ligand (Scheme 4.3a). 56,57 Interestingly, the (S,R,R)-ligand gave better enantioselectivities and higher selectivity for the (4+3)-cycloadduct over the (3+2)-cycloadduct compared to when the (R,R,R)-ligand was used. The authors propose that the Pd-catalyst oxidatively adds into the cyclopropane ring at the distal bond to form a metallocyclobutane 4.3d (Scheme 4.3b).…”
Section: Palladium Platinummentioning
confidence: 99%
“…An enantioselective version of the above [3+2]-cycloaddition has been later reported by the same group starting from unsaturated ACPs. [83] The best results were obtained by using the bulky phosphoramidite ligand (S,R,R)-L10 (Scheme 41). When the dipolarophile bears a conjugated diene instead of an electron-poor alkene, the [4+3]-cycloaddition is the favored over the [3+2].…”
Section: Alkylidene or Vinyl Cyclopropanes As Heterodipolesmentioning
confidence: 99%
“…An enantioselective version of the above [3+2]‐cycloaddition has been later reported by the same group starting from unsaturated ACPs . The best results were obtained by using the bulky phosphoramidite ligand ( S , R , R )‐ L10 (Scheme ).…”
Section: Heterodipole/heterodipolarophile [⊖–⊕/δ⊕–δ⊖] Interactionsmentioning
confidence: 99%
“…The reaction was then successfully employed in a total synthesis of pyrovellerolactone . Similarly, Pd‐catalyzed intramolecular cyclizations of MCP‐containing molecules to synthesize the heterocycle‐fused cycloheptenes were also achieved …”
Section: Construction Of Medium and Large Carbocyclesmentioning
confidence: 99%